Defining self and other: Bangladesh’s secular aspirations and its writing of islam - Huq, Samia (© 2013 Sameeksha Trust, 2016)
This article was published in the Economic & Political Weekly [© 2013 Sameeksha Trust ] and the definite version is available at : http://www.epw.in/journal/2013/50/revisiting-secularisation-special-issues/defining-self-and-other.html The article website is at: http://www.epw.in/journal